TcbZIP60 positively regulates pyrethrins biosynthesis in Tanacetum cinerariifolium - Xu, Zhizhuo; Zeng, Tuo; Li, Jiawen; Zhou, Li; Li, Jinjin; Luo, Jing; Zheng, Riru; Wang, Yuanyuan; Hu, Hao; Wang, Caiyun (Frontiers in Plant Science, 2023)
Pyrethrins, synthesized in the perennial plant Tanacetum cinerariifolium, are a class of terpene mixtures with high insecticidal activity and low human toxicity, which are widely used in plant-derived pesticides. Numerous studies have identified multiple pyrethrin biosynthesis enzymes, which can be enhanced by exogenous hormones such as methyl jasmonate (MeJA). However, the mechanism by which hormone signaling regulates pyrethrin biosynthesis and the potential involvement of certain transcription factors (TFs) remain unclear. In this study, we found that the expression level of a TF in T. cinerariifolium was significantly increased after treatment with plant hormones (MeJA, abscisic acid). Subsequent analysis identified this TF as a member of the basic region/leucine zipper (bZIP) family and was thus named TcbZIP60. TcbZIP60 was localized in the nucleus, suggesting that it is involved in the transcription process. The expression profiles of TcbZIP60 were similar to those of pyrethrin synthesis genes in different flower organs and at different flowering stages. Furthermore, TcbZIP60 could directly bind to the E-box/G-box motifs in the promoters of the pyrethrin synthesis genes TcCHS and TcAOC to activate their expression. Transient overexpression of TcbZIP60 increased the expression levels of pyrethrin biosynthesis genes, leading to the significant accumulation of pyrethrin. Silencing of TcbZIP60 significantly downregulated pyrethrins accumulation and related gene expression levels. Overall, our results reveal a novel TF, TcbZIP60, that regulates both the terpenoid and jasmonic acid pathways of pyrethrins biosynthesis in T. cinerariifolium.